Biomimetics for architecture : learning from nature - Knippers, Jan; Schmid, Ulrich, 1957-; Speck, Thomas (Birkhäuser, 2019)
Nature has always been a source of inspiration for the design of the human environment. The analysis of biological constructions can not only lead to astonishing technical solutions but can also inspire the design of architecture. Bionics is a fascinating border area between pure research and practical application: biologists, chemists, physicists, mineralogists, and paleontologists meet up with material scientists, engineers, and architects and transfer their knowledge to architecture and construction. Using numerous practical examples, this richly illustrated introduction traces the process from the understanding of how something functions, to abstraction-for example in computer models-and the construction of initial prototypes, through to fully functional manufacture and production.